(untitled) (Research, Society and Development, 2021)
Objective: to analyze the presence and triggering factors of suicidal behavior in college students. Methodology: research descriptive exploratory, qualitative, application of digital survey with information social-demographic, mental health, suicidal behavior, analyses of referential content. Participation, 34 college students. Results: majority below 21 years old, single, female, white, no children, enrolled in the first three semesters, individual income up to R1.000,00, family income up to R2.000,00, unemployed, financial hardships; family history of mental disturb and suicidal behavior; 22 participants had suicidal behavior, majority with suicidal thoughts, 12 recurrent thoughts, some life-risk behavior, 12 practice mutilation, 5 planned suicide, one attempt suicide, one had previous treatment. Predisposing factors: relationships and relatives, mental disturbs; trigger factors: low self-esteem, financial hardships, stressed circumstances, sadness, impulsiveness. Conclusion: most of the participants presented suicidal behavior, present and repetition of suicidal behavior and risky behavior, none was receiving professional health increasing suicidal risk.